The Effect of Licorice roots powder on experimental Infection of infectious bursal disease in broiler chickens: A.K.Kassab and Muhannad.F.Humood - Kassab, A. K. (The Iraqi Journal of Veterinary Medicine, 2006)
This study was conducted to investigate the effect of Licorice roots powder for 35 days in reducing the severity of infection with infectious bursal disease (IBD)and the immune response and performance of broiler chicks .A Total of 150 day old broiler chickens were divided into 5 groups and treated as follows :Group 1: infected with IBD virus at 21 days of age. Group 2: infected with IBD virus at 21 days of age and given 1 gm of Licoriceroots powder /1 L of drinking water one day after infection . Group 3 : given 1 gm Licorice roots powder / 1L of drinking water at day oneof age and infected with IBD virus at day 21 of age . Group 4:given 1 gm Licorice roots / 1 L of drinking water at 22 days of age.Group 5: untreated control. Antibody (Ab) of IBD titer was measured by ELIZA , the serum total protein (STP) the serum Globulin(SG)and the blood picture were determined , the water content of the droppings was measured , the body weight , food intake was recorded, there was increase (P<0.01) in the (Ab)titer of IBD virus in the group3 comparing with the other groups , the bursa / body weight index (B:BW)three days after infection was increased (P<0.01) in group1 , the STP , the SG , the PCV and RBCs was increased (P<0.01) in group 3 at age 27 days the food intake (FI) Food conversion ratio (FCR) and body weight (BW) in Group 3 weresignificantly increased , the dropping water content was significantly (P<0 .01)increased in group 3 in comparison with other groups at the period from 23-27 days of age, the morbidity and Mortality rate were significantly lower in group 3 and then 2 in comparison with group 1 (50 % , 63.3 %, 90 % ) and (6.6% , 16.6 % ,30%) respectively